Chitosan Derivatives/Calcium Carbonate Composite Capsules Prepared by the Layer-by-Layer Deposition Method. (13th February 2008) - Sasaki, Takashi; Shimizu, Misato; Wu, Yusong; Sakurai, Kensuke
Abstract : Core/shell capsules composed of calcium carbonate whisker core (rod-like shape) and chitosan/chitosansulfate shell were prepared by the layer-by-layer deposition technique. Two chitosan samples of different molecular weights (M w = 9.7 × 10 4 and1.09 × 10 6 g · mol - 1 ) were used as original materials. Hollow capsules were also obtained by dissolution of the core in hydrochloric acid. Electron microscopy revealed that the surface of the shell is rather ragged associated with some agglomerates. The shell thicknessl obeys a linear relation with respect to the number of deposited layersm asl = m d + a ( a > 0 ) . The values ofd (thickness per layer) were 4.0 and 1.0 nm for the higher and lowerM w chitosan materials, respectively, both of which are greater than the thickness of the monolayer. The results suggest that the feature of the deposition does not obey an ideal homogeneous monolayer-by-monolayer deposition mechanism. Shell crosslinked capsules were also prepared via photodimerization reaction of cinnamoyl groups after a deposition of cinnamoyl chitosan to the calcium carbonate whisker core. The degree of crosslink was not enough to stabilize the shell structure, and hollow capsule was not obtained.